Distribución Poisson-Pascal generalizada utilizando el algoritmo de Panjer (2010)
Panjer’s algorithm used in the calculation actuarial basis taking class distributions (a,b), presents a recursive formula for calculating function distribution of sums of random variables in a model of collective risk. If the secondary distribution in this model is the ETNBD, Compound Poisson distribution is named PoissonPascal, this is a family of distributions very used in the mathematics of insurance and can generate models statistically appropriate. It illustrates the methodology application to a data set of a portfolio of policies cars, in addition the algorithm is implemented using the statistical software R.